The mediolateral center of pressure movement differs between training and racing shoes: a case study - Moore, S. R.; Martínez, A.; Schwameder, H.; Stöggl, T. (ISBS Proceedings Archive (Michigan), 2023)
Athletes that compete on an elite level often employ running shoes specifically for racing that contain carbon plating. The purpose of this case study was to compare one female athlete`s mediolateral COP while she ran in racing and training shoes. SPM analyses revealed several regions where significant differences existed (pp<0.05) for both left and right footfalls. While the magnitude of the differences observed in the right foot appear to be minimal, the difference in the left footfalls indicate that the athlete is experiencing a lesser magnitude of medial COP displacement with the training shoe. The athlete therefore appears to be compensating by limiting foot pronation when using her training shoe. As a result, it is important to investigate mediolateral COP when characterizing movement patterns and compensations of athletes using multiple shoes.